Kaji sifat fisik biokomposit polylactic acid berpenguat serbuk cangkang kerang lokan - Alqap, A. Sofwan F; Hestiawan, Hendri; Suandi, Agus; Zuliantoni, Zuliantoni; Farid, Muhammad (TURBO [Tulisan Riset Berbasis Online], 2023)
This research aimed to investigate the effect of adding lokan clam shell powder on the physical properties of polylactic acid (PLA) biocomposites. The research materials consisted of lokan clam shells obtained from the fish auction place in Pulau Baai of Bengkulu City, PLA in filament form, and chloroform. Lokan clam shells were washed with clean water, dried for 12 hours and heated at 900oC for 6 hours. The powder obtained was filtered using a 100 mesh sieve. The PLA dissolution process used chloroform for 2 hours in a closed process with a ratio of 1 g PLA to 5 ml chloroform. After that, added lokan clam shell powder and stirred for 15 minutes using a hotplate at room temperature. The biocomposite manufacturing process used a molding technique with variations in the volume fraction of lokan clam shell powder of 10%, 30% and 50%. The physical properties test includes the density test using the ASTM standard of D1622 and the water absorption test using the ASTM standard of D 570. The results of the physical properties research show that the addition of 10% lokan shell powder to the PLA biocomposite is able to reduce the density and increase the maximum water absorption by 0 .89 g/cm3 and 5.91% respectively.